Telegram (draft) - Citrine, Walter, 1887-1983
013-0013-001 27.11.42 DEVRIESI SOUTH AFRICAN TRADES AND LABOUR COUNCIL 31 PRITCHARD STREET JOHANNESBURG HAVE ALREADY MADE STRONGEST REPRESENTATIONS TO GOVERNMENT. WALTER CITRINE. 292/946/13/13